2018
DOI: 10.1021/acs.iecr.8b02541
|View full text |Cite
|
Sign up to set email alerts
|

Batch and Fixed Bed Biosorption of Copper by Acidified Algae Waste Biomass

Abstract: The aim of this work is to investigate the biosorption of Cu(II) by an acidified waste product from the alginate extraction of algae in batch system and fixed bed columns. The results showed that the maximum copper biosorption capacity verified for the acidified biosorbent at 313 K was 3.580 mmol g −1 and equilibrium isotherms were best described by the Dubinin−Radushkevich model. Thermodynamic analysis showed that the process presented positive values of biosorption enthalpy (22.91 kJ mol −1 ) and biosorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 62 publications
3
3
0
Order By: Relevance
“…Furthermore, it can be observed in Table 1 that the effective diffusion coefficients decrease as the concentration is increased, which corroborates with the results obtained in the intraparticle diffusion model, where there is an increase in the effect of the boundary layer (c) with the initial concentration, implying greater resistance to mass transfer and consequently less effective diffusion. This directly proportional relationship between the boundary layer and the initial concentration of the metallic solution, also observed by Freitas et al (2018) in the removal of copper using the same biosorbent, which indicates that the increase in aluminum concentration is directly related to the increase in external resistance to mass transfer. The better adjustment of the EMTR model rather than the DI model to the kinetic data, for all concentrations tested, ratifies that the According to Giles et al (1960) classification, the initial slope of the isotherms obtained is classified as H type, which suggests that the metal has elevated affinity for the biosorbent material.…”
Section: Biosorbent Characterizationsupporting
confidence: 63%
“…Furthermore, it can be observed in Table 1 that the effective diffusion coefficients decrease as the concentration is increased, which corroborates with the results obtained in the intraparticle diffusion model, where there is an increase in the effect of the boundary layer (c) with the initial concentration, implying greater resistance to mass transfer and consequently less effective diffusion. This directly proportional relationship between the boundary layer and the initial concentration of the metallic solution, also observed by Freitas et al (2018) in the removal of copper using the same biosorbent, which indicates that the increase in aluminum concentration is directly related to the increase in external resistance to mass transfer. The better adjustment of the EMTR model rather than the DI model to the kinetic data, for all concentrations tested, ratifies that the According to Giles et al (1960) classification, the initial slope of the isotherms obtained is classified as H type, which suggests that the metal has elevated affinity for the biosorbent material.…”
Section: Biosorbent Characterizationsupporting
confidence: 63%
“…Furthermore, it can be observed in Table 1 that the effective diffusion coefficients decrease as the concentration is increased, which corroborates with the results obtained in the intraparticle diffusion model, where there is an increase in the effect of the boundary layer (c) with the initial concentration, implying greater resistance to mass transfer and consequently less effective diffusion. This directly proportional relationship between the boundary layer and the initial concentration of the metallic solution, also observed by Freitas et al (2018) in the removal of copper using the same biosorbent, which indicates that the increase in aluminum concentration is directly related to the increase in external resistance to mass transfer. The better adjustment of the EMTR model rather than the DI model to the kinetic data, for all concentrations tested, ratifies that the process is predominantly governed by diffusion in external film.…”
Section: Effect Of Phsupporting
confidence: 63%
“…Costa et al (2016) found that the process of alginate obtainment using the brown algae Sargassum filipendula generates a residue that still preserves several functional groups identical to those found in raw alga and directly linked to the ion exchange mechanism of the biosorption process. Several studies point to this residue as a promising biosorbent in the uptake of toxic and precious metals, in addition to being also efficient in removing emerging pollutants (Freitas et al 2018;Cardoso et al 2020;Coelho et al 2020;Moino et al 2020). Furthermore, the use of waste as an adsorbent material has less environmental impact compared to traditional adsorbents like activated carbon (Nishikawa et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, sericin/ alginate/poly(vinyl alcohol)-based biocomposite particles were examined for the removal and recovery of lanthanum from aqueous medium. The use of the waste protein obtained from the textile industry during processing of silk yarns and alginate extracted from brown seaweed, which is widely available off the Brazilian coast, is advantageous because the costs involved are low and this biomass is naturally abundant and renewable [ 31 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%